Self Theorist: Pengaruh Teori Diri terhadap Motivasi, Kepribadian, dan Pengembangan Diri - Wardani, Silvia; Asbari, Masduki; Misri, Miftahul Jannah (Journal of Information Systems and Management (JISMA), 2024)
This article is a review which is a critical reading of a guidebook that inspires and provides motivation, personality and self-development for its readers, in a book entitled "Self-Theorist" by Carol S. Dweck, discussing self-theory, mindset, and its influence on various aspects of human life. Carol S. Dweck suggests that self theory is the beliefs we have about ourselves, including our abilities, potential and worth. This study method is descriptive qualitative with content analysis techniques on the book object "Self Theorist". From this book we can learn that it is important to understand yourself and increase your potential. This book offers a deep understanding of self and mindset theory, as well as strategies to help people develop a growth mindset. Carol S. Dweck suggests that mindset has a significant influence on motivation, personality and self-development. What is the meaning of Motivation?, How to get yourself motivated?, What are the theories of personality and motivation? These questions will be answered in this book. By integrating the latest psychological theories, "Self Theories" offers a valuable contribution for readers who are interested in understanding more deeply how self-views can shape a person's life journey. This book is not only relevant for professionals in the fields of psychology and education, but also for anyone who wants to explore their full potential in personal development and achieving life goals.